On the role of density fluctuations in the core turbulent transport of Wendelstein 7-X. (1st April 2022) - Carralero, D; Estrada, T; Maragkoudakis, E; Windisch, T; Alonso, J A; Velasco, J L; Ford, O; Jakubowski, M; Lazerson, S; Beurskens, M; Bozhenkov, S; Calvo, I; et al.
Abstract: A recent characterization of core turbulence carried out with a Doppler reflectometer in the optimized stellarator Wendelstein 7-X (W7-X) found that discharges achieving high ion temperatures at the core featured an ITG-like suppression of density fluctuations driven by a reduction of the gradient ratio η i = L n / L T i (Carralero et al 2021 Nucl. Fusion 61 096015). In order to confirm the role of ITG turbulence in this process, we set out to establish experimentally the relation between core density fluctuations, turbulent heat flux and global confinement. With this aim, we consider the scenarios found in the previous work and carry out power balance analysis for a number of representative ones, including some featuring high ion temperature. We also evaluate the global energy confinement time and discuss it in the context of the ISS04 inter-stellarator scaling. We find that when turbulence is suppressed as a result of a reduction of η i, there is a reduction of ion turbulent transport, and global performance is improved as a result. This is consistent with ITG turbulence limiting the ion temperature at the core of W7-X. In contrast, when turbulence is reduced following a decrease in collisionality, no changes are observed in transport or confinement. This could be explained by ITG modes being combined with TEM turbulence when the latter is destabilized at low collisionalities.